Equity valuation : Hugo Boss - Megre, Martim Aragão Morais (2018)
The purpose of this dissertation is to value Hugo Boss AG, a Germany-based company engaged in the manufacturing and sale of premium and luxury fashion and accessories for men and women under HUGO and BOSS brand names. After an extensive analysis of the company and apparel industry, three methods were performed to value Hugo Boss: Discounted Cash-Flow, Dividend Discount Model and multiples. Each one contributes to the final target price, being DCF the most relevant one, with a target price of €88,45. Notwithstanding, the final target price was €82,80, which represents an upside of 16,71% comparing to the share price as of 29th December 2017. Therefore, a Buy recommendation was given to investors. Lastly, the results were compared to the ones given by a research note from Societe General as of 20th December 2017, and the main differences were analysed.